Thermal Behavior Variations among Commercial Gutta-percha Brands: An Optical Thermography Study - Uzal, Moisés; Aranguren, José; Perez, Alejandro R.; Ramírez-Muñoz, Ana; Navarrete, Natalia (Iranian Endodontic Journal, 2025)
Introduction: This study aimed to assess the thermal behavior of five different commercial gutta-percha brands using optical thermography. We focused on temperature differences and heat transfer characteristics at different apical distances. Materials and Methods: Gutta-percha cones from the following brands were tested: Autofit Greater Taper, Protaper Gold F2, TruNatomy Prime, ZARC Gutta-percha points # 25/0.06, and Reciproc Blue R25. A specific heating system was used to subject the cones to thermal imaging. Measurements were taken at 1-, 2-, 3-, and 4-mm apical distances for 5 mm and 10 mm cone lengths. Statistical analyses included Student’s t-tests and Analysis of Variance with the significance level set at 0.05. Results: Upon intragroup comparison, we found subtle distinctions in thermal behavior when examining gutta-percha cone lengths (5 mm versus 10 mm). TruNatomy exhibited statistically significant variations (P<0.05) at 2- and 3-mm distances. Conversely, ZARC and Reciproc Blue R25 displayed notable differences (P<0.05) at 2-, 3-, and 4-mm distances. In contrast, Autofit Greater Taper and Protaper Gold F2 consistently diverged across all distances (P<0.05). In intergroup comparisons of 5 mm length, significant variances (P<0.05) emerged among brands at 1- and 2-mm distances. At 10 mm length, TruNatomy differed significantly (P<0.05) from other brands across all distances. The heat tip maintained an average maximum temperature of 154.54°C. Conclusion: Thermal behavior of gutta-percha brands varied significantly, with implications for endodontic treatments. While differences were observed in heat transfer and maximum temperatures, all brands remained within safe temperature ranges for clinical use. Understanding these variations can aid clinicians in selecting appropriate gutta-percha for specific clinical scenarios, ultimately optimizing root canal obturation quality.